2002
DOI: 10.1016/s0896-6273(02)00713-4
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Bidirectional Plasticity of Parallel Fiber Receptive Fields in Cerebellar Purkinje Cells and Their Afferent Interneurons

Abstract: The highly specific relationships between parallel fiber (PF) and climbing fiber (CF) receptive fields in Purkinje cells and interneurons suggest that normal PF receptive fields are established by CF-specific plasticity. To test this idea, we used PF stimulation that was either paired or unpaired with CF activity. Conspicuously, unpaired PF stimulation that induced long-lasting, very large increases in the receptive field sizes of Purkinje cells induced long-lasting decreases in receptive field sizes of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
284
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(328 citation statements)
references
References 33 publications
30
284
4
Order By: Relevance
“…Unfortunately, most physiological studies to date have used single distinct stimuli (Bower and Woolston 1983;Garwicz et al 1998;Jorntell and Ekerot 2002;Shambes et al 1978). Although for the sake of control and analysis (and eventual comparison to experimental data), we have only extended the current study to paired-pulse responses, recent recordings have demonstrated that activity in the granule cell layer consists of complex ongoing temporal patterns in awake behaving rats (Hartmann and Bower 2001).…”
Section: Functional Consequences For the Cerebellummentioning
confidence: 96%
“…Unfortunately, most physiological studies to date have used single distinct stimuli (Bower and Woolston 1983;Garwicz et al 1998;Jorntell and Ekerot 2002;Shambes et al 1978). Although for the sake of control and analysis (and eventual comparison to experimental data), we have only extended the current study to paired-pulse responses, recent recordings have demonstrated that activity in the granule cell layer consists of complex ongoing temporal patterns in awake behaving rats (Hartmann and Bower 2001).…”
Section: Functional Consequences For the Cerebellummentioning
confidence: 96%
“…Therefore, in eyeblink conditioning, the US will activate both pathways. USrelated mossy fiber-parallel fiber activity may thus contribute to mechanisms of cerebellar cortical plasticity (Jörntell and Ekerot, 2002;Ekerot and Jörntell, 2003). CNQX application suppressed both periocular-evoked mossy and climbing fiber responses in periocular microzones.…”
Section: Periocular Microzones In Lobule Hvi Are Critical For Expressmentioning
confidence: 99%
“…For example, when parallel fiber input is weak or absent (as in the present work), then a substantial proportion of GABAergic signals will be excitatory, thus maintaining a relatively high IN firing rate. If, on the other hand, the parallel fiber input is strongly activated (as it does in vivo after certain stimulation protocols; Jörntell and Ekerot, 2002), GABAergic synapses will turn inhibitory, and the overall effect on IN firing will be dampened. In this way, the ability of GABAergic synapses to change signs adds flexibility to the network and allows it to maintain its mean firing rate in the range in which it reacts best to new information.…”
Section: A Self-regulating Network?mentioning
confidence: 99%